Teaching Materials Based on Ethnomathematics of Muaro Jambi Temple - Maryono; Sastrawati, Eka; Budiono, Hendra; Destrinelli (International Journal of Elementary Education, 2024)
The mathematics teaching materials teachers use are complex for students to understand, and there needs to be elements of cultural content. Based on this, this research aims to develop flat-building teaching materials based on the ethnomathematics of Muaro Jambi Temple. This type of research is development research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The methods used to collect data are observation, interviews, questionnaires, and tests. The instruments used to collect data were questionnaire sheets and test questions. The validation stage is divided into two stages: validation 1 by three experts (material, design, and language) and validation 2 by the teacher to see the practicality of the teaching materials. The data analysis technique uses qualitative and quantitative descriptive analysis. The research results showed that the validation of material experts with presentations was 83.5%, design experts 86.7%, and language experts 85.2%. The teacher's practicality test obtained 77%, and the student's response to the teaching materials obtained a presentation of 90%. The validation results show that the teaching materials developed are efficient in the mathematics learning process and meet valid and practical criteria. It was concluded that the Muaro Jambi Temple ethnomathematics-based flat building teaching materials were suitable for learning.